THE EFFECT OF WATER EXTRACT OF SOME PLANTS, GROWTH REGULATOR (DIMILLIN) AND METABOLIC PRODUCTS OF RHIZOPUS SP ON GRYLLODES AIGILLATUS - wathah, Esraa fadel; Hatem, Rasha Muzahim (Pakistan Journal of Biotechnology, 2018)
This research aimed to investigate the activity of the Ricius Communis, Dodonia sp. and Syzygium Aromaticum extract plants, growth regulator(Dimillin) and fungal suspension of Rhizopus sp. on both Nymph and adult stages of Gryllodes sigillatus insect. The excellence of Rhizopus sp. fungal suspension had been noticed in nymph stage destruction, in which it reached 96.82% in 100% concentration after 6days from the treatment, while the effect of Dimillin reached 90.22% in the same concentration. As for the extract plants the R. communis followed by Dodona sp. and Syzygium S. S. aromaticum were more effective in spraying than in feeding, in which they reached 87.22%, 75.12% and 69.13% successively through spraying, while they reached 64.2%, 53.4% and 48.1% successively respectively through feeding. In adult stages the mortality proportion of the fungus reached 81.14% in 100% concentration. The growth regulator hadn’t any mortality proportion in adults, in nymphs the R. communis plant is the most effective through spraying in which it reached 72.4% in 40% concentration after 6 days from the treatment.